Advanced resources for plant genomics: a BAC library specific for the short arm of wheat chromosome 1B - Janda, Jaroslav; Safár, Jan; Kubaláková, Marie; Bartos, Jan; Kovárová, Pavlína; Suchánková, Pavla; Pateyron, Stephanie; Cíhalíková, Jarmila; Sourdille, Pierre; Simková, Hana; Faivre-Rampant, Patricia; Hribová, Eva; et al. (The Plant journal, 2006)
Common wheat (Triticum aestivum L., 2n = 6x = 42) is a polyploid species possessing one of the largest genomes among the cultivated crops (1C is approximately 17 000 Mb). The presence of three homoeologous genomes (A, B and D), and the prevalence of repetitive DNA make sequencing the wheat genome a daunting task. We have developed a novel 'chromosome arm-based' strategy for wheat genome sequencing to simplify this task; this relies on sub-genomic libraries of large DNA inserts. In this paper, we used a di-telosomic line of wheat to isolate six million copies of the short arm of chromosome 1B (1BS) by flow sorting. Chromosomal DNA was partially digested with HindIII and used to construct an arm-specific BAC library. The library consists of 65 280 clones with an average insert size of 82 kb. Almost half of the library (45%) has inserts larger than 100 kb, while 18% of the inserts range in size between 75 and 100 kb, and 37% are shorter than 75 kb. We estimated the chromosome arm coverage to be 14.5-fold, giving a 99.9% probability of identifying a clone corresponding to any sequence on the short arm of 1B. Each chromosome arm in wheat can be flow sorted from an appropriate cytogenetic stock, and we envisage that the availability of chromosome arm-specific BAC resources in wheat will greatly facilitate the development of ready-to-sequence physical maps and map-based gene cloning.
Keywords: chromozomy rostlin; genom rostlinný; Chromosomes, Plant; Triticum; Genome, Plant; pšenice; Chromosomes, Artificial, Bacterial; umělé bakteriální chromozomy